Electromagnetic ion cyclotron waves in the subsolar region under normal dynamic pressure: Wind observations and theory - Farrugia, C.J. (2004)
Fil:Gnavi, G. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.